Exploring Contemporary Issues and Key Takeaways: A Comparative Analysis of Civil-Law Notary Laws in Indonesia and Louisiana - David Tan; Agustianto Agustianto; Sovina Sovina (Universitas Internasional Batam, 2023)
Notary as a public official authorized to make authentic deeds in each country has its own rules by adhering to the civil law and common law legal systems, this is specially true for Indonesia and Louisiana which have similarities in adhering to the civil law legal system. This study aims to compare the legal arrangements of notaries in Indonesia and Louisiana where to examine contemporary issues or important points found from legal comparisons. This method uses a type of normative legal research with a comparative approach, statute approach, and conceptual approach made from primary and secondary laws, which are collected using document research techniques in a description analysis. The results and findings of this comparative analysis are that there are significant differences related to notaries from countries that both adhere to the civil law legal system, this can be seen in terms of history, qualifications, duties and authorities to become a notary, sanctions and resolutions for violations that will occur. This legal difference raises interest in the realm of notaries which is expected through this research can be one of the supporting sources for the Indonesian state to discover the findings of notaries in various jurisdictions so as to improve positive law and or at least form a deeper body of knowledge in the field of notaries.